An Alternative Method for Solving Lagrange's First-Order Partial Differential Equation with Linear Function Coefficients (Journal of Partial Differential Equations, 2015)
" An alternative method of solving Lagrange's first-order partial differential equation of the form $$(a_1x+b_1y+c_1z)p+(a_2x+b_2y+c_2z)q=a_3x+b_3y+c_3z,$$ where p=\u2202z\/\u2202x, q=\u2202z\/\u2202y and a_i, b_i, c_i (i=1,2,3) are all real numbers has been presented here."